ПОВЕДЕНЧА ГНУЧКІСТЬ ЯК УМОВИ УСПІШНОСТІ ПРОФЕСІЙНИХ ДІЙ МЕНЕДЖЕРА ОСВІТИ (Педагогіка вищої та середньої школи, 2008)
In clause the essence of behavioral flexibility, as one of the important conditions of professional actions of the manager of formation reveals. Aspects of professional competence of the manager of formation are staticized.